A clinimetric analysis of the Pressure Ulcer Risk Primary or Secondary Evaluation Tool: PURPOSE-T. (14th November 2019) - Wynn, Matthew; Holloway, Samantha
Abstract : The assessment of patients' risk for developing pressure ulcers is a routine and fundamental nursing process undertaken to prevent avoidable harm to patients in all care settings. Many risk assessment tools are currently used in clinical practice, however no individual tool is recommended by advisory bodies such as the National Institute for Health and Care Excellence or the European Pressure Ulcer Advisory Panel. The evidence base on the value of structured risk assessment tools in reducing the incidence or severity of pressure ulcers is poor. This purpose of this article is to provide a clinimetric analysis of the recently developed Pressure Ulcer Risk Primary or Secondary Evaluation Tool (PURPOSE-T) and identify areas for future research to improve the utility of structured risk assessment in identifying patients at risk of developing pressure ulcers.